1994
DOI: 10.2337/diab.43.2.318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NIDDM on the Kinetics of Whole-Body Protein Metabolism

Abstract: We postulated that dietary protein utilization and body protein metabolism are altered in hyperglycemic individuals with non-insulin-dependent diabetes mellitus (NIDDM). This was tested by estimating the kinetics of protein metabolism in obese NIDDM patients in the hyperglycemic state of isoenergetic feeding and in the normoglycemic state induced by the prolonged use of a very-low-energy diet (VLED) and comparing them with results in obese nondiabetic subjects studied previously. Seven obese subjects with NIDD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 36 publications
0
19
1
Order By: Relevance
“…Previous studies in CF have demonstrated increased protein catabolism [14,15] and studies by our group [16] and others [17,18] have described resistance to insulin's anti-catabolic effect on protein breakdown (i.e. they need more insulin to suppress protein catabolism than a non-CF person, yet they are insulin deficient) [2].…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies in CF have demonstrated increased protein catabolism [14,15] and studies by our group [16] and others [17,18] have described resistance to insulin's anti-catabolic effect on protein breakdown (i.e. they need more insulin to suppress protein catabolism than a non-CF person, yet they are insulin deficient) [2].…”
Section: Introductionmentioning
confidence: 95%
“…Several studies have shown increased urinary N loss and net whole-body protein loss in type 2 diabetic patients, even those who are hyperinsulinemic (Gougeon et al 1994(Gougeon et al , 1997(Gougeon et al , 1998. Halvatsiotis et al (2002) found no difference in plasma amino acid concentrations between type 2 diabetic patients from whom insulin treatment was withdrawn transiently and patients who were given intensive insulin treatment for 11 days, except for a reduction in the glycine levels in the untreated patients.…”
Section: Introductionmentioning
confidence: 95%
“…In moderately hyperglycemic obese subjects with type 2 diabetes compared with an obese control group, Gougeon et al [7] reported that during a weight-maintaining diet with ample protein intake, protein metabolism is accelerated. In contrast to subjects without diabetes, euglycemia from a very low-energy diet did not completely re-establish nitrogen equilibrium in subjects with type 2 diabetes.…”
Section: Type 2 Diabetesmentioning
confidence: 97%
“…Fortunately, the large amount of protein in the customary diet of persons with diabetes compensates for the increased protein catabolism, and thus protects them from protein malnutrition [7].…”
Section: Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation